2021
DOI: 10.3390/min11030294
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Microstructures of Phyllite in Gunsan, Korea, and Implications for Seismic Anisotropy in Continental Crust

Abstract: Muscovite is a major constituent mineral in the continental crust that exhibits very strong seismic anisotropy. Muscovite alignment in rocks can significantly affect the magnitude and symmetry of seismic anisotropy. In this study, deformation microstructures of muscovite-quartz phyllites from the Geumseongri Formation in Gunsan, Korea, were studied to investigate the relationship between muscovite and chlorite fabrics in strongly deformed rocks and the seismic anisotropy observed in the continental crust. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
(182 reference statements)
1
3
0
Order By: Relevance
“…As expected, the variations of 2D seismic velocities in the x 1– x 2 plane increase with increasing modal percentage of aligned mica (Figure 7b). Similarly, 3D seismic anisotropies of P and S waves ( AV P and AV SH shown in Figure 7c) increase with mica modal percentage, which is consistent with previous work (e.g., Almqvist et al., 2021; Christensen, 1965; Dempsey et al., 2011; Han & Jung, 2021; Kästner et al., 2021; Ward et al., 2012). We calculate velocity contrasts of these synthetic microstructures relative to the synthetic QF rock at ϕ = 0°.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, the variations of 2D seismic velocities in the x 1– x 2 plane increase with increasing modal percentage of aligned mica (Figure 7b). Similarly, 3D seismic anisotropies of P and S waves ( AV P and AV SH shown in Figure 7c) increase with mica modal percentage, which is consistent with previous work (e.g., Almqvist et al., 2021; Christensen, 1965; Dempsey et al., 2011; Han & Jung, 2021; Kästner et al., 2021; Ward et al., 2012). We calculate velocity contrasts of these synthetic microstructures relative to the synthetic QF rock at ϕ = 0°.…”
Section: Discussionsupporting
confidence: 90%
“…However, the rocks juxtaposed across the SCSZ are intensely deformed mylonite/ultramylonite and highly sheared schist. Such deformation can affect the intensity and pattern of seismic anisotropy and hence elastic contrast if it changes the strength of mica crystallographic preferred orientation, operates certain slip systems in minerals such as basal <a>, rhomb <a> or prism <a> slip in quartz (e.g., Han & Jung, 2021; Ji et al., 2015; Mainprice & Casey, 1990; McDonough & Fountain, 1993; Ward et al., 2012), and develops structures such as S‐C fabrics, crenulations and folds (e.g., Lloyd et al., 2009; Naus‐Thijssen, Goupee, Johnson, et al., 2011). For example, during long‐term tectonic deformation, mylonitization typically generates a strong macroscopic foliation, which may increase seismic anisotropy owing to transition to C‐type fabric from S‐C fabric during deformation (e.g., Kern & Wenk, 1990; Lloyd et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The factor that can affect the seismic anisotropy in amphibolite include the deformation strength, modal composition of amphibole and other minerals with strong single crystal seismic anisotropy like biotite and muscovite (Han & Jung, 2021; Ji et al., 2013; Kitamura, 2006; Lamarque et al., 2016; Tatham et al., 2008). Minerals like quartz and plagioclase commonly appeared in amphibolite were reported to dilute the seismic anisotropy when considering the entire rock as displayed in this study and previous work (Huang et al., 2022; Tatham et al., 2008; Wang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that in the middle to lower crust seismic anisotropies are mainly controlled by the CPOs of constituent mineral phases in a rock aggregate (Ji et al., 2013; Rasolofosaon et al., 2000). Amphibole and micas (e.g., biotite and muscovite) are likely to be the principal contributors to seismic anisotropy of the deeper continental crust due to their strong single crystal seismic anisotropy and strong CPO strength developed (Dempsey et al., 2011; Han & Jung, 2021; Ji et al., 2013, 2015; Lloyd et al., 2009; Mahan, 2006; Tatham et al., 2008). Studies of naturally deformed amphibole‐containing samples have also shown that the modal composition of amphibole, deformation strength, magmatic flow, and partial melting can have significant impacts on seismic anisotropy (Kang & Jung, 2019; Shao et al., 2021; Tatham et al., 2008; Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%